Masa Depan Sastra Di Era Digital: Kajian Sastra Sibernetik - Rizal, Moh. Ahsan Shohifur; Kholik, Kholik; Faizi, Ahmad; Kholiq, Abdul; Azizan, Yoga Rifqi (Innovative: Journal Of Social Science Research, 2024)
The digital era has brought significant changes to various aspects of life, including in the world of literature. The emergence of digital technology has given rise to various new platforms for creating and enjoying literary works, such as social media, blogs, and e-book platforms. This raises questions about the future of literature in this digital era. This study aims to explore how digital technology influences the form, content, and way of enjoying literary works. This study uses a cybernetic literary approach to analyze the interaction between literature and digital technology. The results of the study show that digital technology has various positive and negative impacts on literature. On the one hand, digital technology opens up new opportunities for literary creators to reach a wider audience and interact with readers directly. On the other hand, digital technology also raises concerns about the potential for cultural homogenization and the loss of humanist values ​​in literary works. This study has important implications for literary theory and practice in the digital era. The findings of this study can help literary creators to understand and utilize the opportunities offered by digital technology, as well as to overcome the challenges faced in this digital era.